2017
DOI: 10.1111/bjc.12127
|View full text |Cite
|
Sign up to set email alerts
|

Guided parent‐delivered cognitive behaviour therapy for children with anxiety disorders: Outcomes at 3‐ to 5‐year follow‐up

Abstract: Objectives. Brief guided parent-delivered cognitive behaviour therapy (CBT) has been developed to meet the demand for non-intensive interventions for children with anxiety disorders, and initial trials have shown it to be effective for children with a range of anxiety disorders. This study examined outcomes 3-5 years post-treatment.Design. A long-term follow-up (LTFU) cohort study.Methods. Families who (1) completed at least 50% of allocated treatment sessions of guided parent-delivered CBT for childhood anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This information, along with observations relating to why parents may or may not feel comfortable talking to their child about the trauma, are of potential importance when designing low-dose, parent-led interventions, which would most likely include the encouragement of conversations between parent and child. A first-line, cost-effective parent-delivered CBT has already been developed for children with anxiety , with the majority (60%) of treatment gains maintained at a three to five year follow-up (Brown et al, 2017). In the PTSD field, parent-focused interventions also show significant promise for children exposed to acute trauma (Berkowitz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information, along with observations relating to why parents may or may not feel comfortable talking to their child about the trauma, are of potential importance when designing low-dose, parent-led interventions, which would most likely include the encouragement of conversations between parent and child. A first-line, cost-effective parent-delivered CBT has already been developed for children with anxiety , with the majority (60%) of treatment gains maintained at a three to five year follow-up (Brown et al, 2017). In the PTSD field, parent-focused interventions also show significant promise for children exposed to acute trauma (Berkowitz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating with respect to the potential benefits of engaging parents in psychological interventions for children, with parent-focused interventions being increasingly utilised in the child mental health field (e.g. Brown et al, 2017;Cobham, Filus, & Sanders, 2017;Creswell et al, 2017). There has been growing interest in low-dose, parentfocused prevention/intervention programs in the context of child PTSS (Berkowitz, Stover, & Marans, 2011;Marsac, Kassam-Adams, Hildenbrand, Kohser, & Winston, 2010).…”
Section: 伤叙述任务描述为一个可以与孩子开始对话,了解孩子的感受以及让孩子处理创伤的机 会。然而,对于一些父母或孩子来说,这项任务mentioning
confidence: 99%
“…ADIS-C/P CSR diagnostic recovery rates at 6-month FU were comparable for both treatment conditions (76% for full guided, 71% for brief guided). Improvements for the intervention conditions were maintained at 3-to 5-year FU (Brown et al, 2017). Waters et al (2013) [32] N = 37.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…This allowed a focus on experiences and outcomes associated with GPD-CBT specifically. Of the 65 families that took part in follow-up assessments (see Brown et al, 2017), 39 parents consented to participate, all of whom participated in in-depth interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The approach has also been found to be cost-effective compared to an alternative brief psychological therapy for child anxiety disorders (Creswell et al, 2017). Furthermore, long-term follow-up studies have shown that few children who recover following GPD-CBT with relapse in subsequent years (Brown et al, 2017). Thus, GPD-CBT could fit within a stepped care model where low-intensity treatments are routinely offered for mild–moderate presentations while more intensive treatments are reserved for those presenting with severe anxiety disorders and those who do not respond to low-intensity interventions (Bower & Gilbody, 2005).…”
mentioning
confidence: 99%